BAG6 variant rs805303 is nominally associated with acei-induced cough among Filipinos - Reganit, Paul Ferdinand M.; Nevado Jr., Jose B.; Cutiongco ? de la Paz, Eva Maria C.; Taquiso, Jezreel L.; Aman, Aimee Yvonne Criselle L.; Llanes, Elmer Jasper B.; Magno, Jose Donato A.; Ona, Ignacia D.; Punzalan, Felix Eduardo R.; Santos, Lourdes Ella G.; Tiongco II, Richard Henry P.; Aherrera, Jaime M.; et al. (2020)
Cough is a common side effect of angiotensin converting enzyme inhibitor (ACEi) therapy. The incidence of ACEi-induced cough has been shown to correlate with genetic variation among different populations. This study aimed to determine the association of candidate genetic polymorphisms with ACEi-induced cough among Filipinos. Two hundred twenty (220) participants on ACEi therapy pressure-lowering in an unmatched case-control study (82 cases with ACEi-induced cough and 138 controls). Genomic DNA samples were extracted and genotyped for selected genetic variants. The association of genetic variants and clinical factors with ACEi-induced cough was determined using regression analyses. Univariate logistic regression showed that the BAG6 variant rs805303 is nominally associated with ACEi-induced cough among Filipinos, at a per-comparison error rate (PCER) of 0.05 (OR 2.10, p = 0.016). The association of the variant with ACEi cough was statistically significant after multiple regression analysis (adjusted OR 2.09, p = 0.022) while adjusting for confounding clinical factors (sex, alcohol intake, and diastolic blood pressure). Further studies are needed to validate these findings. (Author's abstract)